Shipping Healthy Calves - Eddie J. Richey (EDIS)
This document is VM106, one of a series of the Veterinary Medicine-Large Animal Clinical Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date March 28, 2000.